Quando l’universalismo fallisce. Fulda sulla deriva del neokantismo di Rickert - Danzilli, Sabato (——— Materialismo Storico ——— Rivista di filosofia, storia e scienze umane, 2026)
This essay provides a context for Hans Friedrich Fulda’s critique of the philosophical views on values expressed by Heinrich Rickert within neo-Kantianism. Through a discussion of internal tensions found in Rickert’s view of universalism, the text presents Fulda’s reading as an immanent critique of neo-Kantianism and a warning about the vulnerability of liberal philosophical systems to exclusionary uses of “values.” Neo-Kantianism; Heinrich Rickert; Hans Friedrich Fulda; Philosophy of values; Nationalism.